COVID-19 und Nierenbefall - Amann, Kerstin Ute; Boor, P.; Wiech, T. (Nephrologe, 2020)
Apart from the pulmonary disease, acute kidney injury is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could also be detected in renal tissue. Patients with chronic kidney disease and on dialysis as well as kidney transplantation patients represent a particularly vulnerable population. The increasing number of patients infected with SARS-CoV‑2 has aroused increased interest in the exact pathophysiology and morphology of kidney damage as well as the direct detection of the virus in the kidneys, which in contrast to the lungs is overall more difficult to perform. Meanwhile, data from several large autopsy and kidney biopsy studies are now available. While the detection of SARS-CoV‑2 RNA in tissue leads to consistently reproducible results, the use of electron microscopy for visualization of the virus is critically discussed due to various artefacts. The exact and direct effects of SARS-CoV‑2 on the kidneys are not yet known in detail and are currently the focus of intensive research.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Acute renal insufficiency; Acute tubular injury; Chronic kidney disease; Coronavirus; Virus detection